HETEROSIS STUDY FOR YIELD COMPONENTS IN CHILLI (CAPSICUM ANNUUM L.) - KANHAIYA LAL PATEL; D. SHARMA; N. MEHTA (The Bioscan, 2015)
Magnitude of heterosis was estimated by Line × Tester analysis including 18 F 1 cross combinations using 9 parents (six lines and three testers) after selfing. These 27 genotypes (6 lines and 3 testers and resulting 18 F 1 hybrids) were evaluated for growth and yield contributing traits. Analysis of variance for Line x Tester analysis for green fruit yield and its components revealed significant differences among genotypes. The magnitude of variance for Line x Tester analysis revealed that the gca variance were relatively higher than the sca variance for all the characters. The relative heterosis for green fruit yield per plant ranged from -9.68 percent (2011-07xLCA-334) to 52.46 percent (2010-03xKA-2) and 2011-03xKA-2 (52.46%) exhibited highest significant positive relative heterosis for this trait. The extent of heterobeltiosis ranged from -22.32 percent (2011-07xLCA-334) to 51.14 percent (2011-03xKA-2) and 2011-03xKA-2 (51.14%) showed highest significant positive heterobeltiosis for this trait. The heterosis over check variety for green fruit yield per plant varied from -25.28 percent (2011-07xIndira Chilli- 1) to 51.14 percent (2011-03xKA-2) and 2011-03xKA-2 (51.14%) exhibited significant positive standard heterosis over check variety for this trait. The most promising crosses showing significantly standard heterosis for maximum yield were 2010-03xKA-2 followed by 2010-06xIndira Chilli-1, 2010-03xLCA-334 and 2011-03xLCA-334.